2020
DOI: 10.1111/jipb.12982
|View full text |Cite
|
Sign up to set email alerts
|

ZmSRL5is involved in drought tolerance by maintaining cuticular wax structure in maize

Abstract: Cuticular wax is a natural barrier on terrestrial plant organs, which protects plants from damages caused by a variety of stresses. Here, we report the identification and functional characterization of a cuticular‐wax‐related gene, Zea mays L. SEMI‐ROLLED LEAF 5 (ZmSRL5). The loss‐of‐function mutant srl5, which was created by a 3,745 bp insertion in the first intron that led to the premature transcript, exhibited abnormal wax crystal morphology and distribution, which, in turn, caused the pleiotropic phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Germplasm with up-curling leaves have been used in rice and maize genetic improvement for elevating cereal crops yield [31]. To find the method to improve canola variety yield, our previous studies have mapped two loci associated with up leaf curling (BnUC1 and BnUC2) onto chromosome A05 of rapeseed (Brassica napus L.) [2,38], and our present study reports a new B. napus line NJAU-M1295 with up-curling leaves (Bnuc3).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Germplasm with up-curling leaves have been used in rice and maize genetic improvement for elevating cereal crops yield [31]. To find the method to improve canola variety yield, our previous studies have mapped two loci associated with up leaf curling (BnUC1 and BnUC2) onto chromosome A05 of rapeseed (Brassica napus L.) [2,38], and our present study reports a new B. napus line NJAU-M1295 with up-curling leaves (Bnuc3).…”
Section: Introductionmentioning
confidence: 82%
“…Leaf curling has also been utilized in maize breeding for compact plant types. Six mutants have been characterized in maize with leaf curling traits [31,50]. In soybean, mutants with rolled leaves and genes/QTL associated with rolled leaves have been reported [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of function of this gene resulted in enhanced drought tolerance. Pan et al ( 2020 ) reported that the gene ZmSRL5 is very vital for a cuticular wax structure, which protects the maize plant from different stresses. Loss of functional mutant progenies of maize showed that the ZmSRL5 gene involved in drought response by keeping the structure of cuticle wax intact.…”
Section: The Era Of Plant Genome Editingmentioning
confidence: 99%
“…A recent significant discovery of the cloning of the Leaf Gas Film 1 ( LGF1 ), a wax synthesis gene involved in the leaf hydrophobicity and formation of the gas films necessary for gas exchange and underwater photosynthesis, is another important step towards developing flood-tolerant varieties [ 311 ]. There is evidence that cuticular wax accumulation is associated with drought tolerance in wheat [ 232 ], maize [ 357 ], and beans [ 358 ]. The dynamics of wax accumulation in leaves of wheat have been recently elucidated [ 359 ].…”
Section: Explored Mechanisms Of Abiotic Stress Tolerance For Crop Improvementmentioning
confidence: 99%